2022
DOI: 10.3390/cancers14163876
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Biomarkers of Response to Neoadjuvant Chemotherapy in Breast Cancer: Current and Future Perspectives for Precision Medicine

Abstract: Pathological complete response (pCR) after neoadjuvant chemotherapy in patients with early breast cancer is correlated with better survival. Meanwhile, an expanding arsenal of post-neoadjuvant treatment strategies have proven beneficial in the absence of pCR, leading to an increased use of neoadjuvant systemic therapy in patients with early breast cancer and the search for predictive biomarkers of response. The better prediction of response to neoadjuvant chemotherapy could enable the escalation or de-escalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 207 publications
0
26
0
Order By: Relevance
“…Livingston-Rosanoff et al reported a retrospective study that included 38,864 patients who underwent NAC treatment and subsequent surgery for a solitary lesion varying from cT1 to cT3, which revealed that cT3 tumors have a lower probability of achieving pCR irrespective of molecular subtypes [ 22 ], which is consistent with our study. The possible explanation for this finding is that larger tumors have a higher chance of revealing heterogeneity of elevation, which may affect the sensitivity of chemotherapy [ 37 ]. Many prediction models involved clinical tumor staging (tumor size) as a predictive factor [ 38 , 39 , 40 ], which indicates it is a reliable factor for predicting pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Livingston-Rosanoff et al reported a retrospective study that included 38,864 patients who underwent NAC treatment and subsequent surgery for a solitary lesion varying from cT1 to cT3, which revealed that cT3 tumors have a lower probability of achieving pCR irrespective of molecular subtypes [ 22 ], which is consistent with our study. The possible explanation for this finding is that larger tumors have a higher chance of revealing heterogeneity of elevation, which may affect the sensitivity of chemotherapy [ 37 ]. Many prediction models involved clinical tumor staging (tumor size) as a predictive factor [ 38 , 39 , 40 ], which indicates it is a reliable factor for predicting pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Livingston-Rosanoff et al reported a retrospective study that included 38,864 patients who underwent NAC treatment and subsequent surgery for a solitary lesion varying from cT1 to cT3, which revealed that cT3 tumors have a lower probability of achieving pCR irrespective of molecular subtypes [20], which is consistent with our study. The possible explanation for this nding is that larger tumors have a higher chance of revealing heterogeneity of elevation, which may affect the sensitivity of chemotherapy [21]. Many prediction models involved clinical tumor staging (tumor size) as a predictive factor [22][23][24], which indicates it is a reliable factor for predicting pCR.…”
Section: Clinical Tumor Stagingmentioning
confidence: 99%
“…In recent years, an increasing number of clinical studies have focused on targeted therapies. Neoadjuvant therapy (NAT) has become a standard clinical practice used to downsize the tumor and increase the breast‐conserving surgery rate 4 . The addition of herceptin on top of chemotherapy increased the pathological complete response (pCR) rate to 38%, 5 and after intervention with both herceptin and pertuzumab, the pCR rate increased to approximately 70% 6 .…”
Section: Introductionmentioning
confidence: 99%